Women in legislatures: Gender, institutions, and democracy (2018)
Leslie A. Schwindt-Bayer and Santiago Alles argue that the influx of women into Latin American legislatures has been substantial, but once in office, women have struggled to attain full access to political power. They present a statistical analysis that shows that the main explanations for variation in women’s representation lie with gender quotas and party system fragmentation. They show that women in national legislatures have brought women’s issues to the legislative arena, and they provide a new analysis showing that female legislators are more supportive of liberal gender equality, abortion, and divorce laws. However, they argue that women have not gained access to diverse committee leadership posts or served in top chamber leadership posts to the same extent as men. Finally, they show that the presence of women in legislatures has had important effects on citizen support for female political leaders, political engagement and participation, and supportiveness of representative democracy. © Oxford University Press 2018.